Evaluation of Intellectual Capital in terms of gender issues - Gottwald Dalibor; Švadlenka Libor (Information Engineering Research Institute, 2015)
Intellectual capital (component of intellectual capital) is currently very topical phenomenon that affects almost all fields of human activity. In the last few years there have been huge increases in studies that seek find the most suitable quantifiers, which would express the extent of components of intellectual capital affect on company or society in general. The research of the actual topic – intellectual capital in respect to gender issues, which are undoubtedly another major topic of current debate, bring a new views to the evaluation of global trends in the world market. Each analysis of these current phenomena, which is based on current data, it is beneficial for every branch of science that is affected by these phenomena.
Hodnocení intelektuální kapitálu v kontextu problematiky genderu
Keywords: Intellectual capital; Education; Gender; Earnings.; Intelektuální kapitál; Vzdělání; Gender; Příjmy